BOARD DIVERSITY REGULATIONS AND PERFORMANCE OF COMMERCIAL BANKS IN KENYA: A CASE OF NAIROBI COUNTY - Karanja, George Kahindi; Awuor, Dr. Emmanuel (European Journal of Business and Strategic Management, 2017)
ABSTRACT Purpose: The purpose of the study was to assess the implementation of board diversity regulations and its effect on performance of commercial banks in Kenya: a case study of Nairobi County Methodology: This study employed a descriptive design. The sampling technique was a census where the sample involved the human resource directors, Chief finance officers and Chief executive officer of all the 43 commercial banks where 129 respondents were the sample size. This study used primary data for independent variables and both primary and secondary data for the dependent variable. Quantitative data collected was coded and evaluated using SPSS version 21. Inferential statistics (correlation and regression) was used. The study also employed a multivariate regression model to study the correlation. Results: Based on the study findings, the study concluded that the professional diversity, gender diversity, minority group diversity and nationality diversity regulations have influence on performance of commercial banks in Kenya. Unique Contribution to Theory, Policy and Practice: Based on the findings of the study, this research recommends that banks review their policies on board diversity regulations to include members from different nationalities, ethnicities and also different ages and gender. Further, banks are recommended to adopt the set government policies on diversity management in boards. Keywords: Professional diversity, gender diversity, minority group diversity and nationality diversity and Performance.